The Sphinx’s riddle: cardiovascular involvement in autoimmune rheumatic disease - Mavrogeni, Sophie (BMC Cardiovasc Disord, 2016)
Factors leading to Cardiovascular Disease (CVD) in Autoimmune Rheumatic Diseases (ARD) include: a) atherosclerosis and macro-microvascular coronary artery disease b) pericardial, myocardial and vascular inflammation c) heart valve disease d) heart failure and e) pulmonary hypertension. Cardiology utilizes various non-invasive imaging modalities, such as rest/stress Electrocardiogram (ECG), echocardiography, nuclear imaging and more recently Cardiovascular Magnetic Resonance (CMR) to detect ischemic or inflammatory disease in ARD. Exercise ECG is a reliable prognostic test for identification of patients either very unlikely or very likely to have cardiac events. However, this is not the case for intermediate risk patients. In stress echocardiography the diagnostic end point for the detection of myocardial ischemia is the induction of a transient worsening in regional function during stress. It provides similar diagnostic and prognostic accuracy as radionuclide stress perfusion, but at a lower cost and without radiation exposure. Stress Myocardial Perfusion Scintigraphy (MPS) is a non-invasive imaging modality for patients with suspected coronary artery disease, but has important limitations including radiation exposure, imaging artefacts and low spatial resolution, which preclude detection of small myocardial scars commonly found in ARD. By identifying early stages of inflammation and perfusion defects, CMR can shed light on the exact pathophysiologic background of myocardial lesions, even if the underlying ARD seems stable. However, high cost and lack of availability and expertise limit wider adoption. Hopefully, CMR will not have the same fate as Oedipous, who despite answering the Sphinx’s riddle successfully, finally came to a bitter end; for in the case of CMR overcoming fate is, in fact, in our hands.